The effect of flash card games on knowledge and attitudes toward diarrhea prevention among elementary school students - M. Farizan Ulthika; Muhammad Naswir; Andree Aulia Rahmat; Willia Novita Eka Rini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Diarrhea remains one of the environment-related diseases that poses a public health problem, particularly among elementary school-aged children. A lack of knowledge and awareness regarding diarrhea prevention can increase the risk of diarrhea in children. One preventive measure that can be taken is providing health education using innovative media such as flashcard games. Purpose: to determine the effect of flashcard games on elementary school students’ knowledge and attitudes toward diarrhea prevention. Method: This study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group. The sample consisted of 102 respondents, comprising an experimental group and a control group, selected through purposive sampling. Data were collected using pre-test and post-test questionnaires and analyzed using the Paired T-test, Wilcoxon test, and Mann-Whitney U test. Result: The results of the study indicate that there was a significant difference in knowledge levels between before and after the intervention in the experimental group (p < 0.001). There was also a significant difference in attitudes between before and after the intervention (p < 0.001). Additionally, there was a significant difference in the change in knowledge between the experimental and control groups (p < 0.001) and a significant difference in the change in attitudes between the experimental and control groups (p < 0.001). Conclusion: Flashcard games have an impact on improving elementary school students’ knowledge and attitudes toward diarrhea prevention. Suggestion: Schools are encouraged to utilize innovative educational tools, such as flashcard games, in their health education programs.Health workers are encouraged to collaborate with schools in implementing health promotion initiatives focused on preventing diarrhea.